Health visitors' awareness and perception of clinical genetic services. Issue 8 (August 1990) - Guilbert, P; Cheater, F
Abstract : A questionnaire was sent to 84 health visitors to assess their awareness and perception of genetic services and how they perceived their role in the referral of patients. The study showed that while health visitors had a reasonable knowledge of the more obvious aspects of genetic services, there were a number of areas in which they were unsure. The respondents did not identify themselves as prime initiators in the process of referring patients to a genetic service, although they appeared able to identify families on their caseloads for whom this service may be relevant. Health visitors viewed their own knowledge of genetics as poor, a factor which may account for the low referral rate initiated by this group of professionals. The respondents attached importance to genetic issues and 76 (95%) wished to be better informed about the subject. It is suggested that the inclusion of genetics as part of an in-service training programme might fulfil this need and lead to greater advocacy of genetic services among the families in their care. These findings are of interest in view of the proposals within the recent Royal College of Physicians report (Prenatal screening and genetic counselling) suggesting that community genetic services should make use of primary health care workers such as health visitors.